2015
DOI: 10.1007/s00421-015-3188-7
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of sensory nerves to cutaneous vasodilatation of the forearm and leg to local skin heating

Abstract: The differences in the initial vasodilatory peak to local skin heating between the forearm and the leg are due to the contribution of sensory nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…We observed that blockade of sensory nerve function (with topical EMLA cream) delayed the onset of vasodilatation, but the difference in the magnitude of the sustained vasodilatory response between limbs persisted (Hodges et al, 2015); however, sensory nerve blockade with EMLA abolished this difference between limbs and greatly increased time to onset of vasodilatation (both~150 s) (Hodges et al, 2015). Additionally, these temporal differences between regions and with sensory nerve blockade occurred for all phases of the local heating response.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…We observed that blockade of sensory nerve function (with topical EMLA cream) delayed the onset of vasodilatation, but the difference in the magnitude of the sustained vasodilatory response between limbs persisted (Hodges et al, 2015); however, sensory nerve blockade with EMLA abolished this difference between limbs and greatly increased time to onset of vasodilatation (both~150 s) (Hodges et al, 2015). Additionally, these temporal differences between regions and with sensory nerve blockade occurred for all phases of the local heating response.…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, the participants were instructed not to eat for 1 h prior to the testing session, but were encouraged to drink water ad libitum. As in our laboratory's previous studies female participants were currently in the low hormone phase of their birth control routine as verified through self-report (Del Pozzi and Hodges, 2015a, 2015b, 2015cHodges et al, 2015).…”
Section: Participantsmentioning
confidence: 89%
See 3 more Smart Citations